Mini-F plasmid mutants able to replicate in the absence of sigma 32: mutations in the repE coding region producing hyperactive initiator protein. - Kawasaki, Y (1991)
Mini-F plasmids cannot replicate in Escherichia coli strains (delta rpoH) lacking sigma 32, presumably because transcription of the repE gene encoding the replication initiator protein (RepE protein) depends mostly on RNA polymerase containing sigma 32. We have isolated and characterized mini-F mutants able to replicate in delta rpoH cells. Contrary to the initial expectation, five mutants with mutations in the repE coding region that produce altered RepE proteins were obtained. The mutations caused replacement of a single amino acid: the 92nd glutamic acid was replaced by lysine (repE10, repE16, and repE25) or glycine (repE22) or the 109th glutamic acid was replaced by lysine (repE26). These plasmids overproduced RepE protein and exhibited very high copy numbers. Two major activities of mutated RepE proteins have been determined in vivo; the autogenous repressor activity was significantly reduced, whereas the initiator activity was much enhanced in all mutants. These results indicate the importance of a small central region of RepE protein for both initiator and repressor activities. Thus the decreased repE transcription in delta rpoH cells can be compensated for by an increased initiator activity and a decreased repressor activity of RepE, resulting in the increased synthesis of hyperactive RepE protein.